MASUKAN SISWA SEBAGAI BAHAN PERBAIKAN KUALITAS KOMPETENSI PEDAGOGIS GURU [STUDENTS' INPUTS AS MATERIALS FOR IMPROVING THE QUALITY OF STUDENT TEACHERS' PEDAGOGICAL COMPETENCE] - Alberthus, Kurnia Henderika; Boangmanalu, Iko Agustina (Polyglot, 2022)
ABSTRACTPedagogic competence that affects learning needs to be continuously improved and this can be done through students’ input which might be used as a source of learning. This study, in particular, aims to describe how students provide input to improve the quality of student teachers’ pedagogical competence. As an image of God, students indeed have been gifted with the ability to provide input for student teachers which can improve the pedagogical competence if there is a follow-up from the student teachers. Student’s input can indeed improve the quality of the teacher’s pedagogic competence when the input is constructive, and teachers are aware of their limitations and are humble enough to receive feedback.  BAHASA INDONESIA ABSTRAKKompetensi pedagogis merupakan kompetensi penting yang memengaruhi pembelajaran, sehingga perlu diperbaiki. Masukan siswa menjadi salah satu sumber belajar mahasiswa guru untuk meningkatkan kompetensi pedagogisnya. Penelitian ini bertujuan menjelaskan cara siswa memberi masukan demi perbaikan kualitas kompetensi pedagogis mahasiswa guru. Siswa adalah ciptaan yang segambar dan serupa dengan Allah sehingga memiliki kemampuan menyampaikan masukan untuk perbaikan kompetensi pedagogis. Siswa dapat memberi masukan untuk perbaikan kualitas kompetensi pedagogis guru menggunakan potensi atau rasionya yang ditindaklanjuti guru secara bijak dengan pertolongan Roh Kudus. Masukan siswa dapat memberi perbaikan kualitas kompetensi pedagogis guru ketika guru menyadari keterbatasannya, memiliki kerendahan hati, dan masukan tersebut jujur dan membangun.KATA KUNCI: Kompetensi pedagogis; Masukan siswa; Guru